Variability in coral reef fish baseline and benchmark biomass in the central and western Indian Ocean provinces. Issue 1 (5th October 2020) - McClanahan, Timothy R.; Friedlander, Alan M.; Graham, Nicholas A. J.; Chabanet, Pascale; Bruggemann, J. Henrich
Abstract: Reef fish biomass is increasingly recognized as a key indicator of fishery and biodiversity status linked to ecosystem integrity on coral reefs, and yet the evaluation of appropriate baselines for biomass, and what drives variation in potential baselines, is sparse. Variability in reef fishable biomass was assessed to test for the existence of baselines or benchmarks (B&Bs), based on field studies of 223 reef sites in remote uninhabited reefs, in high‐compliance closures of >5 km 2, and among the increasing number of small and recent closures. The purpose of the study was to examine the effects of human habitation, travel time and distance to cities, habitat, depth, benthic cover, and environmental variables on fish B&Bs. There were large differences in the three categories of 'no fishing', with human habitation being the single best predictor of biomass. In remote areas without people (>9 hours of travel time), fish biomass had a mean of 2, 450 kg ha –1 (95% confidence interval, 95% CI, 2, 130–2, 770 kg ha –1 ; median = 1, 885 kg ha –1 ). In these remote areas, biomass was weakly associated with human travel time to the site and, to a lesser extent, wave energy. In high‐compliance closures, fish biomass peaked at 20 years and 5–10 km 2, and levelled at 910 kg ha –1 (95% CI 823–989 kg ha –1 ) for both closure age and size. There was little evidence that human travel time and environmental factors influenced biomass greatly in these established closures. In small and recent closures (<15 years), habitat, depth and closure age were the best predictors of fish biomass. Based on the weakness of environmental factors, country or site‐specific B&Bs are not required in these two provinces. However, human habitation in the seascape as well as the size and age of closures set limits to the maximum achievable biomass. The importance of environmental factors increases as the no‐fishing areas and closure times decline. Reef wilderness is not widespread in these provinces, but provides key services and therefore needs to be included in conservation and fisheries policy and management goals.